Metroglyph Analysis in Cotton (Gossypium Sp.) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Pattern of morphological variations was studied in seven cultivars of cotton viz. (1) DPL-41, (2) DPL-20, (3) BAC-49, (4) DPL-50, (5) DPL-51, (6) JA/96-B and (7) DPL-90 by metroglyph and index score method (Anderson, 1957). Two most variable characters - plant height at maturity (PHM) and fibre yield per plant (FYP) were selected for X and Y axis, respectively. In metroglyph diagram there appeared two clusters one comprised of 2 and the other comprised of 3 cultivars. Cluster I representing cultivar nos. 1 and 2 and cluster II cultivar nos. 4, 5 and 7. In both the clusters (Cluster I and II) the members are not so closely associated. In cluster I the members seems to form a straight line and in cluster II they form a triangle. An exceptional feature is the off location of two glyphs representing cultivar nos. 3 and 6. Key words: metroglyph analysis; cotton; Gossypium Bangladesh J. Sci. Ind. Res. 42(4), 449-454, 2007